Alpha7 Nicotinic Acetylcholine Receptor Antagonists Prevent Meningitic Escherichia coli-Induced Blood–Brain Barrier Disruptions by Targeting the CISH/JAK2/STAT5b Axis - Zelong Gong; Xuefeng Gao; Yubin Li; Jinhu Zou; Jingxian Lun; Jie Chen; Chengxing Zhou; Xiaolong He; Hong Cao (Biomedicines, 2022)
Despite the availability of antibiotics over the last several decades, excessive antibiotic treatments for bacterial sepsis and meningitis (BSM) in children may result in several adverse outcomes. Hematogenous pathogens may directly induce permeability increases in human brain microvascular endothelial cells (HBMECs) and blood–brain barrier (BBB) dysfunctions. Our preliminary studies demonstrated that the alpha7 nicotinic acetylcholine receptor (α7nAChR) played an important role in the pathogenesis of BSM, accompanied by increasing cytokine-inducible SH2-containing protein (CISH) at the transcriptome level, but it has remained unclear how α7nAChR-CISH works mechanistically. The study aims to explore the underlying mechanism of α7nAChR and CISH during E. coli-induced BSM in vitro (HBMECs) and in vivo (α7nAChR-KO mouse). We found that in the stage of E. coli K1-induced BBB disruptions, α7nAChR functioned as the key regulator that affects the integrity of HBMECs by activating the JAK2–STAT5 signaling pathway, while CISH inhibited JAK2–STAT5 activation and exhibited protective effects against E. coli infection. Notably, we first validated that the expression of CISH could be regulated by α7nAChR in HBMECs. In addition, we determined the protective effects of MLA (methyllycaconitine citrate) and MEM (memantine hydrochloride) (functioning as α7nAChR antagonists) on infected HBMECs and suggested that the α7nAChR–CISH axis could explain the protective effects of the two small-molecule compounds on E. coli-induced HBMECs injuries and BBB disruptions. In conclusion, we dissected the α7nAChR/CISH/JAK2/STAT5 axis as critical for the pathogenesis of E. coli-induced brain microvascular leakage and BBB disruptions and provided novel evidence for the development of α7nAChR antagonists in the prevention of pediatric E. coli BSM.